Immunological biomarker research in uro-oncology-using the example of urothelial cancer - Eckstein, Markus (Die Urologie, 2022)
The most common malignant tumor of the urinary tract system is urothelial carcinoma (UC). With the introduction of novel immunologic therapy options in both metastatic and localized settings, the exploration of immunologic biomarkers to predict potential treatment success has become a focus of clinical translational research. For example, expression levels of programmed cell death ligand 1 (PD-L1) in UC tumors can help clinicians decide which patients are more likely to respond to immuno-oncology therapies; in light of new approvals with mandated PD-L1 testing (e.g., adjuvant nivolumab therapy after radical cystectomy), harmonization of PD-L1 testing is becoming increasingly important. However, in addition to PD-L1 determination, broader potentially predictive biomarkers such as tumor mutational burden and immune signatures/phenotypes have been and continue to be investigated in clinical trials. This review will provide a streamlined overview of existing evidence and new developments in the field of urothelial carcinoma.
CRIS-Team WoS Importer:2022-09-16